"Handbook of imaginary places": landscape, process, technique and fiction - Almozara, Paula (PORTO ARTE: Revista de Artes Visuais, 2013)
The text discusses issues related to the poetic construction of the series of works entitled "Handbook of imaginary places", product of the institutional research project “landscape-path”. It also presents a report on the processes resulting from hybrid connections between languages and the use of elements of location technologies from ideas that establish a dialogical relation between imagination and reality, in which fictional and documental elements are used to build new possibilities of perceiving and relating with the landscape.